2015
DOI: 10.1182/blood-2014-07-588319
|View full text |Cite
|
Sign up to set email alerts
|

Innovative thrombolytic strategy using a heterodimer diabody against TAFI and PAI-1 in mouse models of thrombosis and stroke

Abstract: • Early thrombolytic treatment with a bispecific inhibitor against TAFI and PAI-1 is effective without exogenous tPA.• Even at the highest dose tested, the bispecific inhibitor against TAFI and PAI-1 does not prolong bleeding time.Circulating thrombin-activatable fibrinolysis inhibitor (TAFI) and plasminogen activator inhibitor-1 (PAI-1) are causal factors for thrombolytic failure. Therefore, we evaluated an antibody-engineered bispecific inhibitor against TAFI and PAI-1 (heterodimer diabody, Db-TCK26D6x33H1F7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 58 publications
1
50
1
Order By: Relevance
“…In a rabbit model of arterial thrombosis, it was shown that several parameters associated with the efficiency of t-PA induced thrombolysis were enhanced and the time to reperfusion was reduced in the presence of the TAFIa inhibitor [56] . Likewise, it had been demonstrated that the combined administration of a heterodimer diabody against TAFI and PAI-1 in mice further decreases the brain lesion volume following rt-PA administration [57] .…”
Section: Discussionmentioning
confidence: 99%
“…In a rabbit model of arterial thrombosis, it was shown that several parameters associated with the efficiency of t-PA induced thrombolysis were enhanced and the time to reperfusion was reduced in the presence of the TAFIa inhibitor [56] . Likewise, it had been demonstrated that the combined administration of a heterodimer diabody against TAFI and PAI-1 in mice further decreases the brain lesion volume following rt-PA administration [57] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in mouse models of thrombotic stroke have shown that simultaneous inhibition of PAI-1 and TAFI with a bispecific antibody results in a significant enhancement of fibrinolysis in mice, without increased bleeding [157]. To dissect out the contribution of PAI-1 inhibition and TAFI inhibition during ischaemic stroke, Denorme et al used monoclonal antibodies to identify the effect of inhibiting each of these antifibrinolytic factors.…”
Section: Current Approaches To Reduce Hypofibrinolysis In Diabetesmentioning
confidence: 99%
“…These results are strongly suggestive for a co-operative effect of PAI-1 and TAFI in ischemic stroke and further support the use of a bispecific diabody targeted against both TAFI and PAI-1. 9 Massberg et al 3 showed that as early as 5 minutes after initiation of reperfusion, fibrin(ogen) is accumulating in the postischemic vasculature, actively recruiting platelets and inflammatory cells. Our findings further support the idea that early fibrin(ogen) generation hampers efficient reperfusion of the affected brain tissue.…”
Section: September 2016mentioning
confidence: 99%
“…7,8 We recently showed a profibrinolytic effect of a novel bispecific inhibitor against TAFI and PAI-1. 9 However, the precise contributions of inhibiting PAI-1 and TAFI during ischemic stroke remain largely unknown. In this study, we therefore used well-characterized monoclonal antibodies (MAs) that inhibit either TAFI or PAI-1 to dissect their role in cerebral ischemia/reperfusion injury.…”
mentioning
confidence: 99%